2012 Benjamin Franklin Medal in Earth and Environmental Science presented to Ellen Mosley-Thompson and Lonnie G. Thompson. Issue 7 (July 2015) - Scatena, Frederick N.; Wehmiller, John F.
Abstract The major contributions of their 35 years of scientific enterprise working together and independently have been: (1) quantifying the dynamics of the global climate system, including millennial scale variations in Monsoons and El Niño Southern Oscillation, the chronology of Late Glacial to present variations in tropical climate, and the role of micro-particles and optical dust in climate; (2) documentation of abrupt climate change and that the current warming trend is faster than anything in the past 5200 years; and (3) the development of ice coring techniques and method of analysis, including collecting and storing the world׳s largest collection of tropical ice cores.